F-Actin Dynamics in the Regulation of Endosomal Recycling and Immune Synapse Assembly - Capitani, Nagaja; Baldari, Cosima T. (Frontiers in Cell and Developmental Biology, 2021)
Membrane proteins endocytosed at the cell surface as vesicular cargoes are sorted at early endosomes for delivery to lysosomes for degradation, or alternatively recycled to different cellular destinations. Cargo recycling is orchestrated by multimolecular complexes that include retromer, retriever and the WASH complex, which promote the polymerisation of new actin filaments at early endosomes. These endosomal actin pools plays a key role at different steps of the recycling process, from cargo segregation to specific endosomal subdomains to the generation and mobility of tubulo-vesicular transport carriers. Local F-actin pools also participate in the complex redistribution of endomembranes and organelles that leads to the acquisition of cell polarity. Here we will present an overview of the contribution of endosomal F-actin to T cell polarization during assembly of the immune synapse, a specialized membrane domain that T cells form at the contact with cognate antigen presenting cells.